THE EFFECT OF LEARNING MATHEMATICS WITH THE NUMBERED HEAD TOGETHER MODEL ON LEARNING OUTCOMES REVIEWED FROM STUDENTS' CREATIVE THINKING ABILITIES - Rania, Nadhifa; Sutarni, Sri (Prima: Jurnal Pendidikan Matematika, 2025)
This study aims to determine the effect of the NHT learning model on students' mathematics learning outcomes, viewed from their creative thinking abilities. The research method used was a quasi-experimental study with a two-group research design, namely the experimental class given the NHT learning model and the control class using the conventional method. The research sample consisted of grade IX students of SMP Negeri 2 Surakarta, who were selected using the cluster random sampling technique. The instruments used included learning outcome tests, creative thinking ability questionnaires, and academic documentation. The data were analyzed using normality tests, homogeneity tests, and two-way analysis of variance.  = 8,151 and  = 4,01 were obtained. Because > , Ho is rejected. Thus, it shows that there is a difference in the effect of implementing NHT and conventional strategies on mathematics learning outcomes.  = 5.655 and  = 3.16 were obtained. Because > , Ho is rejected. So it shows that there is a difference in the influence of students' creative thinking skills on mathematics learning outcomes. Obtained  = 2.446 and  = 3.16. Because  <  then Ho is accepted. So it shows that there is no interaction between the application of NHT and conventional strategies with students' creative thinking skills on mathematics learning outcomes. So it shows that there is no interaction effect of learning models and creative thinking skills on student learning outcomes. So it can be concluded that the Numbered NHT learning model is more effective than the conventional model in improving overall student learning outcomes, and high creative thinking skills make a significant contribution to mathematics learning outcomes. However, the effectiveness of the NHT learning model is not influenced by creative thinking skills.